The political and economic implications of China's interest in Africa: a case study of Angola and Sudan - Judas, Shingange Sekgathane (My University, 2013)
Unable to load abstract
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, School of Social Sciences, Department of International Relations, 2010